Health status in South Australians caring for people with cancer: A population‐based study. Issue 11 (30th August 2019) - Luckett, Tim; Agar, Meera; DiGiacomo, Michelle; Lam, Lawrence; Phillips, Jane
Abstract: Objectives: To compare physical and mental health status between cancer carers versus non‐carers in a population‐based sample and explore sociodemographic and caring characteristics associated with poor carer health status. Methods: The South Australian Health Omnibus is a population‐based cross‐sectional survey. Carer status was self‐defined by participants as having cared for someone with cancer in the last 5 years. Health status was considered poor if it was 0.5 standard deviation lower than Australian norms on the Medical Outcomes Study 12‐Item Short‐Form (SF‐12) physical and mental component summary scores (PCS and MCS). Regression analyses compared mean PCS/MCS between carers versus non‐carers, controlling for sociodemographic variables, and explored associations between poor health status and caring and support among carers. Results: The weighted sample included 2962 people, of whom 374 (12.6%) were cancer carers and 1993 (67.3%) non‐carers. Carers had significantly worse PCS/MCS, controlling for sociodemographic variables, but did not differ significantly regarding proportions with poor health status. Carer characteristics associated with poor PCS and MCS included socio‐economic indicators and involvement in medication management. Assisting with household tasks was protective. Conclusions: This population‐based study followed those previous ones in finding cancer carers to have poorer mean health status than non‐carers. However, differences were less pronounced than previously reported, likely because of the sample being drawn from a general rather than cancer service population and including past as well as current carers, as well as all cancer types and stages. Future longitudinal research is needed to identify factors that predict recovery post caring.